2019
DOI: 10.1128/jvi.00922-18
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Leader Protease Cleaves G3BP1 and G3BP2 and Inhibits Stress Granule Formation

Abstract: Like other viruses, the picornavirus foot-and-mouth disease virus (FMDV; genus Aphthovirus), one of the most notorious pathogens in the global livestock industry, needs to navigate antiviral host responses to establish an infection. There is substantial insight into how FMDV suppresses the type I interferon (IFN) response, but it is largely unknown whether and how FMDV modulates the integrated stress response. Here, we show that the stress response is suppressed during FMDV infection. Using a chimeric recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 62 publications
(75 reference statements)
2
76
1
Order By: Relevance
“…Indeed, infection with EMCV-2A pro , but not EMCV-2Am, resulted in cleavage of eIF4G, while infection with EMCV-3C pro resulted in G3BP1 cleavage. No G3BP1 cleavage was observed in cells infected with either EMCV-L Zn , which is consistent with our previous observations (11,41,42), or EMCV-3Cm.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, infection with EMCV-2A pro , but not EMCV-2Am, resulted in cleavage of eIF4G, while infection with EMCV-3C pro resulted in G3BP1 cleavage. No G3BP1 cleavage was observed in cells infected with either EMCV-L Zn , which is consistent with our previous observations (11,41,42), or EMCV-3Cm.…”
Section: Resultssupporting
confidence: 93%
“…It has been suggested that EMCV 3C pro cleaves G3BP1 and that this prevents SG assembly, although this cleavage is observed only at very late stages of infection (10 to 12 hpi) (40). In contrast, we and others did not observe G3BP1 cleavage in cells infected with either EMCV or Theiler's murine encephalomyelitis virus, and instead provided extensive evidence that the leader protein has an essential role in suppressing SG formation in cardiovirus-infected cells (11,41,42). As part of these studies, we generated EMCV-L Zn , a mutant virus in which the leader protein is inactivated by mutations that disrupt its zinc finger domain and that, as a consequence, can no longer suppress SG formation.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…For rhinoviruses, nothing is known about their capacity to manipulate stress granule formation, however, for other picornaviruses the 2A and L proteases have recently been shown to interfere by cleaving stress granule factors such as G3BP1 and G3BP2 [106][107][108][109]. A recent report showed that binding of eiF4GI translation factor to stress granule-inducing protein G3BP1 is essential for antiviral stress granule formation, and this interaction is disrupted by the 2A or L proteases of picornaviruses [110].…”
Section: Manipulation Of Stress Granule Formationmentioning
confidence: 99%
“…G3BP1, also known as G3BP or HDH-VIII, is a ubiquitously expressed protein and functions as a sequence-specific, phosphorylation-dependent helicase, a cofactor, an endoribonuclease, and more (19). Recently, it has been reported that FMDV L pro and 3C pro may cleave G3BP1 to inhibit stress granule (SG) formation; however, FMDV L pro and 3C pro do not interact with G3BP1 (20,21). This finding prompted us to determine the FMDV proteins that interact with G3BP1 and the mechanism by which it regulates G3BP1 to facilitate FMDV replication and growth.…”
mentioning
confidence: 99%